Elevated Serum Pentosidine and Decreased Serum IGF-I Levels are Associated with Loss of Muscle Mass in Postmenopausal Women with Type 2 Diabetes Mellitus - Tanaka, K.; Kanazawa, I.; Sugimoto, T. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Advanced glycation end-products (AGEs) play important roles in the progression of diabetic complications. Although sarcopenia is recently recognized as another complication associated with diabetes mellitus, its mechanism still remains unclear. In this study, we investigated the relationship between serum levels of pentosidine, which is one of AGEs, and insulin-like growth factor-I (IGF-I) vs. skeletal muscle mass by whole body dual-energy x-ray absorptiometry in 133 postmenopausal women with type 2 diabetes. Relative skeletal muscle mass index (RSMI) was calculated by following formula; appendicular skeletal muscle mass divided by height in meters squared. Simple correlation analyses showed that serum pentosidine levels were significantly and negatively correlated with muscle mass of legs (r=−0.21, p=0.017) and RSMI (r=−0.18, p=0.022), and that IGF-I was significantly and positively correlated with muscle mass of arms and legs (r=0.23, p=0.008 and r=0.30, p=0.001, respectively) as well as RSMI (r=0.20, p=0.022). Moreover, after adjusting for age, duration of diabetes, serum creatinine, HbA1c, and IGF-I, pentosidine was significantly and negatively associated with RSMI (β=−0.27, p=0.018) and marginally with muscle mass of legs (β=−0.18, p=0.071). The associations between IGF-I and indices of muscle mass such as arms, legs and RSMI were still significant after additional adjustment for pentosidine (p=0.016, 0.019 and 0.021, respectively). These findings indicate that increased serum pentosidine and decreased IGF-I are independent risk factors for loss of muscle mass in postmenopausal women with type 2 diabetes.
Keywords: pentosidine; skeletal muscle mass; sarcopenia; diabetes mellitus; IGF-I